(NlI^NOSTX (B: (NTEORII(B, (NUPRAVNENIQ(B, (N\KSPERIMENTY (B/s - (NfREJDVER(B, (NrOBERTs; (Nf\JDIMEN(B, (NdVEJMSs ((NsANKT(B-(NpETERBURG (B:s (NPRAJM(B-(NeWROZNAK (B;s (NmOSKWA (B:s (Nolma(B-(NpRESS(B,s, 2004)
(NpOMIMO KLASSI^ESKIH I SOWREMENNYH TEORIJ LI^NOSTI W U^EBNIK WKL@^ENY WOSTO^NYE KONCEPCII LI^NOSTI(B, (NKOTORYE POZNAKOMQT ^ITATELQ SO WZGLQDAMI NA LI^NOSTX INDUIZMA(B, (NBUDDIZMA I ISLAMA(B.s
(NnA OBL(B.: "(NnA SEGODNQ \TOT U^EB(B.-(NSAMOE POL(B., (NTO^(B. (NI DEMOKRATI^(B. (NIZLOV(B. (NKONCEPCIJ LI^NOSTI(B"s
(NbIBLIOGR(B. (NW KONCE GL(B.s
Keywords: (NpSIHOLOGIQs; (NoB]AQ PSIHOLOGIQs; (NpSIHOLOGIQ LI^NOSTI (B- (Nu^EBNIKIs